Proceedings of the 8th International Multidisciplinary Conference on Optofluidics (IMCO 2018) (Springer, 2021)
This book is a compilation of selected papers from the 8th International Multidisciplinary Conference on Optofluidics (IMCO 2018) held in Shanghai on August 5-8, 2018, as well as papers from the IMCO 2019 held in Hong Kong on June 14-17, 2019. The work focuses on the current development in the fields of optofluidics, microfluidics, silicon photonics, optical metamaterials and other related areas. Readers from both academia and industry will benefit from the experts’ opinion and the lasted development in the multidisciplinary field of optofluidics.